LGBTQI digital media activism and counter-hate speach in Italy. - Gabai, Sara. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
LGBTQI Digital Media Activism and Counter-Hate Speech in Italy analyzes the organizational communication practices of Italian LGBTQI activists. The book investigates digital media activism practices, and how, through artifacts of political engagement, activists are championing social change through non-violent communications. The author also interrogates whether legal means are enough to combat hate and promote a culture of human rights. This book is an essential read for students and scholars interested in LGBTQ rights and activism.
Keywords: Digital media -- Political aspects; Sexual minorities -- Political aspects; Hate speech; Civil rights; SOCIAL SCIENCE -- Gender Studies; SOCIAL SCIENCE / Gender Studies